Intentional Binding Without Intentional Action - Suzuki, Keisuke; Lush, Peter; Seth, Anil K.; Roseboom, Warrick (Psychological Science, 2019)
The experience of authorship over one’s actions and their consequences—sense of agency—is a fundamental aspect of conscious experience. In recent years, it has become common to use intentional binding as an implicit measure of the sense of agency. However, it remains contentious whether reported intentional-binding effects indicate the role of intention-related information in perception or merely represent a strong case of multisensory causal binding. Here, we used a novel virtual-reality setup to demonstrate identical magnitude-binding effects in both the presence and complete absence of intentional action, when perceptual stimuli were matched for temporal and spatial information. Our results demonstrate that intentional-binding-like effects are most simply accounted for by multisensory causal binding without necessarily being related to intention or agency. Future studies that relate binding effects to agency must provide evidence for effects beyond that expected for multisensory causal binding by itself.